Effect of Audit Committee Meetings on Quality of Financial Reporting Among Non-Commercial State Corporations In Kenya - Mwangi, Kirubi (Archives of Business Research, 2023)
The purpose of this study was to establish the effect of audit committee meetings on quality of financial reporting in non-commercial state corporations in Kenya. All the noncommercial state corporations were studied. The study was founded on stewardship theory and the policeman theory. Empirical evidence on influence of audit committees on quality brof financial reporting was reviewed analysed and research gaps identified. The study adopted descriptive research design and used census on all 72 state corporations. The study used primary and secondary data. Primary data was obtained from administration of questionnaires and the secondary data obtained from the Kenya National Audit Office annual reports, Audited Financial statements of state corporations and Finance Bills of the respective financial years. Regression analysis was employed to ascertain existence of relationships between dependent and independent variables. The findings from both correlation and regression analysis revealed that audit committee meetings had statistical significant relationship with the quality of financial reporting. The results revealed that audit committee meetings reduced the ratio of queried transactions to annual budget of non-commercial state corporations in Kenya/p